Comparative genomics of Crohn's disease-associated adherent-invasive Escherichia coli - O'Brien, Claire L; Bringer, Marie-Agnès; Holt, Kathryn E; Gordon, David M; Dubois, Anaëlle L; Barnich, Nicolas; Darfeuille-Michaud, Arlette; Pavli, Paul (Gut, 2017)
ObjectiveAdherent-invasive Escherichia coli (AIEC) are a leading candidate bacterial trigger for Crohn's disease (CD). The AIEC pathovar is defined by in vitro cell-line assays examining specific bacteria/cell interactions. No molecular marker exists for their identification. Our aim was to identify a molecular property common to the AIEC phenotype.Design41 B2 phylogroup E. coli strains were isolated from 36 Australian subjects: 19 patients with IBD and 17 without. Adherence/invasion assays were conducted using the I-407 epithelial cell line and survival/replication assays using the THP-1 macrophage cell line. Cytokine secretion tumour necrosis factor ((TNF)-α, interleukin (IL) 6, IL-8 and IL-10) was measured using ELISA. The genomes were assembled and annotated, and cluster analysis performed using CD-HIT. The resulting matrices were analysed to identify genes unique/more frequent in AIEC strains compared with non-AIEC strains. Base composition differences and clustered regularly interspaced palindromic repeat (CRISPR) analyses were conducted.ResultsOf all B2 phylogroup strains assessed, 79% could survive and replicate in macrophages. Among them, 11/41 strains (5 CD, 2 UCs, 5 non-IBD) also adhere to and invade epithelial cells, a phenotype assigning them to the AIEC pathovar. The AIEC strains were phylogenetically heterogeneous. We did not identify a gene (or nucleic acid base composition differences) common to all, or the majority of, AIEC. Cytokine secretion and CRISPRs were not associated with the AIEC phenotype.ConclusionsComparative genomic analysis of AIEC and non-AIEC strains did not identify a molecular property exclusive to the AIEC phenotype. We recommend a broader approach to the identification of the bacteria-host interactions that are important in the pathogenesis of Crohn's disease.